Pengaruh Promosi, Emosi Positif Terhdap Pembelian Impulsif Pada Marketplace - Kurniawati, Fani; Riorini, Sri Vandayuli; Lestari, Septiani Dwi (Innovative: Journal Of Social Science Research, 2024)
The research methodology employed is an online survey involving respondents from active marketplace users. Data were collected through questionnaires covering inquiries related to promotion, positive emotions, and impulsive buying behavior. Regression analysis will be utilized to identify the extent to which promotion and positive emotions can predict impulsive buying behavior. The findings of this research are expected to provide deeper insights into the factors influencing impulsive buying behavior in the marketplace. The practical implications of this research can assist business practitioners and marketers in developing effective promotional strategies and building positive experiences for consumers, thereby enhancing the potential for impulsive buying.